Penerapan Model Contextual Teaching And Learning (Ctl) Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Materi Siklus Hidup Hewan Kelas Iv - idawidayanti widayanti; Asep Sam (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to improve students' critical thinking skills in science learning material about animal life cycles using the Contextual Teaching and Learning (CTL) model. The subjects in this study were grade IV students with a total of 15 students who were held at SDN Palayangan, Pangalengan District, Bandung Regency for the academic year 2022/2023 Semester 1. Data collection techniques were used through pretest and posttest questions to students, conducting interviews with teachers, giving questionnaires and make observations. The data is used to find the results of quantitative and qualitative data. Data processing is carried out using the SPSS 21 program. Critical thinking is very important in learning so that students are able to solve problems well. Therefore researchers use the Contextual Teaching and Learning model so that learning becomes effective and makes students actively involved in learning and discussing. The learning steps are (a) constructivism, (b) finding, (c) asking, (d) learning communities, (e) modeling, (f) reflection, and (g) real assessment. The results showed that from the pretest and posttest given there was an increase in the critical thinking skills of fourth grade students using the Contextual Teaching and Learning model to 70%. From these results it shows that the Contextual Teaching and Learning model used has a good influence on students' critical thinking skills in science learning in elementary schools. In this study, I used mixed research methods which included qualitative and quantitative research, which differed from each other.